2013
DOI: 10.4028/www.scientific.net/kem.589-590.173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drills with Different Drill Bits on Delamination in Drilling Composite Materials

Abstract: Drilling is frequently used in machining of carbon fiber reinforced materials. Twist drill is mostly used in drilling composite materials and some other drills with special drill bits are also needed. Drilling induced delamination is considered one of the most serious problems during machining while drilling force plays a decisive role in delamination. This paper presents the analysis of critical thrust force with special drill bit theoretically. The method of simulation to study the critical thrust force is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It was revealed that the main abrasive wear was the wear mechanism which then contributes to increasing the temperature gradually and subsequently, affects the final surface topography of the drilled hole. Wei et al [48] developed a mathematical model based on classical plate bending theory and linear elastic fracture mechanics to conduct the analysis of the drill bits on the delamination of CFRP. It was concluded that large feed speed contributed more in the occurrence of delamination.…”
Section: Drilling Process On Carbon Fiber Reinforced Polymermentioning
confidence: 99%
See 2 more Smart Citations
“…It was revealed that the main abrasive wear was the wear mechanism which then contributes to increasing the temperature gradually and subsequently, affects the final surface topography of the drilled hole. Wei et al [48] developed a mathematical model based on classical plate bending theory and linear elastic fracture mechanics to conduct the analysis of the drill bits on the delamination of CFRP. It was concluded that large feed speed contributed more in the occurrence of delamination.…”
Section: Drilling Process On Carbon Fiber Reinforced Polymermentioning
confidence: 99%
“…Twist drills [45,46,53,52,48,118] Brad & spur drills [119] Step drills [52,120] Straight-flute drill bit [121,122] Slot drill bit [65] Saw drills [116] Dagger drill [123] Candlestick drill [116] Core drills [109] Core-twist drill [124] Core-saw drill [124] Step-core-candlestick drill [124] Core-candlestick drill [124] Step-core-twist drill [124] Step-core-saw drill [124] Countersink drill [51] Tapered drill reamer [125] Reamer drill with four cutting edges [126] Figure 10: Drill tool geometries used in CFRP For instance, Brad & spur drills were recommended by [119], step drills were used by [52,120], dagger drills by [123], saw drills by [116] , core drills by [109], Slot drill bit by [65], candlestick drill by [116], core-twist drill, core-saw drill, step-core-candlestick drill, core-candlestick drill, step-core-saw drill, and step-core-twist drill were used by [124], countersink drill by [51], and tapered drill reamer was used by [125]. Figure 7 shows some of them schematically [127].…”
Section: Role Of Drill Tool Geometry Tool Materials and Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Special issues may arise from the serious subsurface damage, irreparable inter-ply delamination, rapid tool wear and heat generation. 710 Especially, the severe hole damage and defects produced in CFRP drilling could be considered as the key contributor to the large amount of all part rejections during machining. In CFRP drilling, the machined hole surfaces comprise both conventional hole defects as occurred in metal drilling (e.g.…”
Section: Introductionmentioning
confidence: 99%